A Mobile Sensor Network Tracking Moving Targets in a Dynamic Environment. Issue 5 (2015) - Dang, Anh Duc; Horn, Joachim
Abstract: This paper presents a novel approach to control a mobile sensor network to track moving targets in a dynamic environment. In this approach, we solve two main issues: the sensor splitting and merging control when the number of the targets is changed. The subgroup merging into the main group is controlled by the invariable attractive force field of the virtual leader in the main swarm. In other words, under the effect of this attractive force field, free-sensors can easily reach the main group and become new members in formation of this group. In contrast, subgroups will be split from the existing group to track new targets that appear. The splitting algorithm is built based on the geometry between targets and group position. The members in a split subgroup will connect with their neighbors in order to generate a robust formation without collision while tracking their target. In addition, when a target disappears, the sensors that are tracking this target will automatically distribute into the nearest existing subgroup. The effectiveness of this proposed approach has been verified in simulations.